2018
DOI: 10.1002/bjs5.50106
|View full text |Cite
|
Sign up to set email alerts
|

Population-based cohort study of the impact on postoperative mortality of anastomotic leakage after anterior resection for rectal cancer

Abstract: BackgroundAnastomotic leakage following anterior resection for rectal cancer may result in death. The aim of this study was to yield an updated, population‐based estimate of postoperative mortality and evaluate possible interacting factors.MethodsThis was a retrospective national cohort study of patients who underwent anterior resection between 2007 and 2016. Data were retrieved from a prospectively developed database. Anastomotic leakage constituted exposure, whereas outcome was defined as death within 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 33 publications
2
85
2
Order By: Relevance
“…In a New Zealand cohort of 233 patients undergoing LAR for benign and malignant diseases, patients who developed AL had higher 30-day mortality as compared to patients without AL (6% versus 1%, p < 0.05) as well as LOS, which was approximately two times higher in AL patients [19]. In another study conducted in Sweden, which included 6,948 patients who underwent anterior resection, the Odds Ratio (OR) for 90-day mortality was 5.57 (95% CI: 3.29–9.44) when patients with major leaks (when a reintervention was performed) versus those with no leaks were compared [23]. From the economic standpoint, our results show a heavy financial burden associated with AL.…”
Section: Discussionmentioning
confidence: 99%
“…In a New Zealand cohort of 233 patients undergoing LAR for benign and malignant diseases, patients who developed AL had higher 30-day mortality as compared to patients without AL (6% versus 1%, p < 0.05) as well as LOS, which was approximately two times higher in AL patients [19]. In another study conducted in Sweden, which included 6,948 patients who underwent anterior resection, the Odds Ratio (OR) for 90-day mortality was 5.57 (95% CI: 3.29–9.44) when patients with major leaks (when a reintervention was performed) versus those with no leaks were compared [23]. From the economic standpoint, our results show a heavy financial burden associated with AL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that the AL rate after rectal cancer surgery is 3% to 26%[ 10 - 12 ]. The occurrence of AL prolongs hospitalization time, increases the economic and mental burden for patients and increases short-term morbidity and mortality[ 13 , 14 ]. Poor blood supply is an important factor in AL.…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage (AL) is one of the most serious and devastating post-operative complications of colorectal cancer surgery. AL has an incidence of 3–27% and a mortality rate of 25–37% [1,2,3,4,5,6]. It is an adverse risk factor for long-term outcomes in these patients [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%